Meningkatkan Filantropi Melalui Crowdfunding: Usulan Fitur Donasi Otomatis di Dompet Dhuafa - Annida Rizki Luthfi Astuti; Rahmatun Nazila; Siti Muslichah; Ala Asmaul Husna; sumarsono (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2024)
The development of technology is inseparable from modernization. Modernization positions itself as a continuous form of globalization. Indonesia is very heterogeneous, and all aspects of society, culture, and life are becoming increasingly diverse along with globalization. The development of technology is the material for modernizing diversity, in order to adjust it in the context of dependence on new technologies, one of which is social computing. Crowdsourcing is part of social computing and is becoming an increasingly popular method among institutions and businesses in all sectors by utilizing community support. This research uses one type of crowdsourcing, namely crowdfunding, which is applied in the dhuafa wallet application. The purpose of this research is to improve the sustainability of social service organizations through the support of the utilization of the wallet dhuafa crowdfunding platform. The method in this research is to use UML and Use Case Diagram to design a system that will display the automatic donation menu and allow users to select the automatic donation category, set the donation time, and view the available balance. The results of this study, by integrating the automatic donation function into the Dompet Dhuafa application, the feature is able to expand its positive impact in helping those in need.